Optimalisasi Kompetensi Guru Dalam Mendesain Dan Menyusun Pembelajaran HOTS Berbasis Merdeka Belajar - Cholifah Tur Rosidah; Danang Prastyo; Wahyu Susiloningsih; Amelia Widya Hanindita (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
There are still many teachers who carry out learning activities that only pursue the quantity aspect of the material. Teachers usually try to convey all the subject matter even in a limited time, thus ignoring the learning process carried out by students. This is not recommended. Learning should not be limited to emphasizing the fulfillment of the quantity of subject matter but must strive to achieve the quality side. Thus the PGSD Adi Buana lecturer team provided assistance to teachers in Gresik district to optimize their competence in designing and compiling learning hots based on independent learning. The method used in the implementation of this community service is a problem-based approach. The results of training and capacity show an increase in the knowledge of skills and abilities of teachers in designing and compiling learning hots based on independent learning. This is indicated by the learning tools collected by the teacher after the mentoring is complete. Teachers are able to arrange learning activities that are able to activate students, provide learning alternatives for students and optimize the competencies possessed by students.